Insertion of long interspersed repeated elements at the Igh (immunoglobulin heavy chain) and Mlvi-2 (Moloney leukemia virus integration 2) loci of rats. - Economou-Pachnis, A (1985)
Restriction enzyme analysis of normal DNA derived from individual rats of the National Institutes of Health outbred Osborn-Mendel colony revealed that two independent single-copy loci, the Igh (immunoglobulin heavy chain) locus and the Mlvi-2 (Moloney leukemia virus integration 2) locus, a putative oncogene, are polymorphic (i.e., exhibit allelic variation). The polymorphism at both loci was due to the presence or absence of a long interspersed repeated DNA element (LINE). The LINE insertion in the Igh locus occurred in the joining (J) region, which is involved in the physiological rearrangement of this locus. The LINE insertion in the Mlvi-2 locus has occurred approximately 6 kilobases from the region of provirus integration in Moloney murine leukemia virus-induced rat thymomas. The two inserts are colinear with each other and with other randomly selected cloned copies of the rat LINE family, the general characteristics of which we also present. LINE insertion in the Mlvi-2 locus was observed in several rat strains, established from independent rat colonies, suggesting that LINE-containing Mlvi-2 alleles may be widespread in the rat population. LINE insertion in the Igh locus was observed in 1 of 27 rats. The detection of a LINE-related polymorphism at two nonselected loci indicates that LINEs are transposable. The presence or absence of these long (greater than 5 kilobases), highly transcribed elements at single-copy loci could have profound effects on gene activity. Furthermore, LINE-containing single-copy loci could be affected by homologous interaction between the resident LINE and any of the other 50,000 or so copies of these elements in the rat genome.